Sleepwear de alto padrão - Volta, Isis Mayssa (2015)
This study aims to present the development of sleepwear pieces that can meet the desires of consumers of the upper classes, starting from the principle that the luxury market is booming and your audience craves differentiated products and increasingly elaborate thus ensuring their economic relationship status on society.